THE EFFECT OF CHAIN DRILL TECHNIQUE ON STUDENTS’ SPEAKING ABILITY (A STUDY AT THE ELEVENTH GRADE STUDENTS’ OF MAS AL-ABRAAR IN 2020/2021 ACADEMIC YEAR) - deri eka putri harahap (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: The purposes of this research are to know: 1) the application of chain drill technique in teaching speaking ability, 2) the students ’speaking ability before and after using chain drill technique, 3) Whether there is any significant effect of chain drill technique on teaching speaking ability at the eleventh grade students of MAS Al-Abraar. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the XI grade students’ of MAS Al-Abraar which consist of 32 students. Sample were also which consist of 32 students which taken by total sampling. In collecting data the researcher uses oral test and observation sheet as an instrument. The result of this research is: 1) the application of chain drill technique was 3.6, it was categorized “Very Good”. 2) the mean score of the students’ speaking ability before using chain drill technique was 50.32 and it was categorized “fail”. Meanwhile, after using chain drill technique was 71.5, it is categorized “Good”. The result of data analysis shows that ttest was higher than ttable (ttest 14.17 > ttable 2.03). So, the hypothesis was accepted. It means that, there is a significant effect of chain drill technique on students’ speaking ability at the eleventh grade students of MAS Al-Abraar in 2020/2021 academic year. Keywords: Chain Drill Technique, Speaking Ability Abstrak:Tujuan dari penelitian ini adalah untuk mengetahui : 1) penggunaan tekhnik chain drill dalam mengajar kemampuan berbicara, 2) kemampuan berbicara siswa sebelum dan sesudah pengaplikasian tekhnik chain drill, 3) apakah ada pengaruh yang signifikan dari tekhnik chain drill terhadap kemampuan berbicara siswa di kelas XI MAS Al-Abraar. Penelitian ini menggunakan metode eksperimental dengan rancangan penelitian pre eksperimental: one group pre-test post-test design. Jumlah populasi terdiri dari 32 siswa dan juga jumlah sampel 32 dengan menggunakan teknik total sampling. Dalam pengumpulan data peneliti menggunakan tes lisan dan lembar observasi sebagai instrument. Hasil dari penelitian yaitu: 1) penggunaan tekhnik chain drill mendapat nilai 3.6 yang dikategorikan “sangat baik”, 2) nilai rata-rata siswa dalam kemampuan berbicara sebelum menggunakan tekhnik chain drill adalah 50.32 dan dikategorikan “gagal”. Sedangkan, setelah penggunaan tekhnik chain drill nilai kemampuan siswa dalam berbicara adalah 71.5 dan dikategorikan “Bagus”. Hasil dari penelitian menunjukkan bahwa ttest lebih tinggi dari ttble (ttest14.17>ttable2.03). hal ini menunjukkan bahwa hipotesis diterima. Dan menunjukkkan bahwa ada pengaruh yang signifikan dari penggunaan tekhnik chain drill terhadap kemampuan berbicara siswa di kelas XI MAS Al-Abraar Tahun Ajaran 2020/2021. Kata kunci: Tekhnik Chain Drill, Kemampuan Berbicara